FINANCIAL AND ECONOMIC MECHANISMS OF ENVIRONMENTALLY SAFE ENTREPRENEURSHIP: LEGAL ASPECT - Gaiovych, Vadym (Socio-economic relations in the digital society, 2020)
The article is devoted to the essence of the concept of such a new type of entrepreneurship as environmental. The aim of the article is to study the conceptual foundations of environmental entrepreneurship in the context of law, financial and economic mechanisms. The article presents different points of view of both Ukrainian and foreign scientists on the concept of «environmental entrepreneurship". At the current stage of development, there is no single universal concept, and, therefore, this means that this concept in Ukraine has relatively recently entered into scientific circulation and still requires refinement.The contradictions between the growing needs of the population and the degradation of the environment indicate the need for a harmonious combination of environmental, economic and financial components of development, shifting the emphasis in favor of the environmental component in the management process.The potential of the legislative and regulatory framework and their effectiveness in stimulating the development of environmental entrepreneurship are analyzed, the organizational and managerial conditions of its development in Ukraine are determined. The scheme of financial and economic mechanism of ecologically safe business in the context of legal regulation is constructed.The theoretical basis on which the financial mechanism of the environmental sphere is based is considered; the role and place of the specified mechanism within the limits of implementation of financial policy of the state are reflected; the legislative bases on which the financial component of the national ecological strategy is based are covered; analytical monitoring of the processes of financial support of environmental protection was carried out. It is proposed to define ecologically safe entrepreneurship as entrepreneurial activity carried out, including in the ecological market, which is aimed at providing people with the cleanest possible products, meeting the needs of society in environmentally friendly living and working conditions. It is substantiated that financial and economic mechanisms from the point of view of regulation of ecologically safe business need to improve the relationship between state authorities and local governments, as their activities in this area are economic management.
Keywords: ecological entrepreneurship; financial mechanism; economical mechanism; natural recourses